The Effect of the Mind Map and the Cooperative Learning Model on Students' Mastery of Arabic Vocabulary at Yamasa Surabaya Middle School. - Masykur, Muhammad Zakki (Journal Of Foreign Language Learning and Teaching, 2022)
Vocabulary is an element of a language. Vocabulary learning is learning where students don't just memorize the vocabulary, but can also use it in communication both in speech and in writing. Mind Mapping is a creative note-taking method using how children's radiant thinking works so that there is a balance between the functions of the two brains. The cooperative learning model is a learning activity in groups to work together to help each other construct concepts and solve problems.The use of mind mapping and cooperative learning models in vocabulary learning aims to make learning fun, not boring, and for students to teach one another, increasing Arabic vocabulary. This study aims to: (1) Determine the effect of mind mapping in increasing the Arabic vocabulary of class VIII SMP Yamassa Surabaya. (2) Knowing the effect of the cooperative learning model on increasing the Arabic vocabulary of Grade VIII students at SMP Yamassa Surabaya. (3) Knowing the effect of mind mapping and cooperative learning models on increasing Arabic vocabulary for class VIII SMP Yamassa Surabaya.This study uses a quantitative approach with multiple linear regression. The sampling technique was carried out randomly, the data was expressed in numbers and analyzed with statistical techniques to test the established hypothesesThe conclusions of this study are as follows: (1) there is an effect of mind mapping on increasing students' Arabic vocabulary by looking at the results of T Count = 3.302 greater than T Table = 2.030 and a significance level of 0.002 less than 0.050. (2) there is an effect of the cooperative learning model on increasing students' Arabic vocabulary by looking at the results of T Count = 2.360 greater than T Table = 2.030 and a significance level of 0.024 less than 0.050. (3) there is an influence between mind mapping and cooperative learning models on increasing students' Arabic vocabulary with the result that F count = 40.250 is greater than F table = 3.23 and a significant point of 0.000 is less than 0.05. It is hoped that this research can make a positive contribution, especially at SMP YAMASSA SURABAYA.